The provision of healthy food in a school tuck shop : does it influence Bloemfontein primary school learners’ perceptions, attitudes and behaviour towards healthy eating - Bekker, Francette (Stellenbosch : Stellenbosch University, 2012)
Thesis (MNutr)--Stellenbosch University, 2012.